2005
DOI: 10.1253/circj.69.466
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Amiodarone-Induced Pulmonary Toxicity in Supine and Prone Positions-High-Resolution Computed Tomography Study-

Abstract: miodarone is a unique anti-arrhythmic drug originally developed for angina. 1 Because of its clinically proven effectiveness, amidodarone is now used to control atrial and ventricular arrhythmias. [2][3][4] Unfortunately, many adverse effects are related to the use of this agent, especially pulmonary toxicity, so called amiodarone-induced pulmonary toxicity (APT). 5,6 The condition of APT is extremely serious and difficult to diagnose, with an incidence of up to 13%. Patients with APT may have an associated mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 24 publications
0
21
0
3
Order By: Relevance
“…As a conclusion, patients undergoing an antiarrythmic therapy with amiodarone featuring the characteristic clin- ical and radiological fi ndings for COP might be treated with corticoids empirically, even without achieving a BAL or invasive lung biopsy before [7,12,16,25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a conclusion, patients undergoing an antiarrythmic therapy with amiodarone featuring the characteristic clin- ical and radiological fi ndings for COP might be treated with corticoids empirically, even without achieving a BAL or invasive lung biopsy before [7,12,16,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In computed tomography (CT) the infi ltrates will be confi rmed with mostly bilateral areas of consolidation and ground-glass opacities [1,2,7,12,16,[24][25][26], which are usually in the periphery, sometimes shaped in the form of triangles (with the base facing the pleura and the tip pointing towards the mediastinum). Further diagnostic means can include BAL and lung biopsy.…”
mentioning
confidence: 99%
“…The side-effects of amiodarone will be assessed by symptoms, chest X-ray, DLco, and KL-6 level every 3 months, 22 and the QOL will be evaluated before randomization and at 12 and 24 months after the initiation of the treatment.…”
Section: Patient Follow-upmentioning
confidence: 99%
“…However, longterm treatment with AM is associated with several adverse effects, the one of greatest concern being AM-induced pulmonary toxicity (AIPT), because it can progress to potentially life-threatening pulmonary fibrosis. Recent studies have reported that the incidence of AIPT occurs in 5 to 13% of patients treated with AM in a dose-and duration-dependent manner (Oyama et al, 2005). The prognosis of a patient with AIPT is poor, with a 10 to 23% mortality rate (Vrobel et al, 1989;Oyama et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that the incidence of AIPT occurs in 5 to 13% of patients treated with AM in a dose-and duration-dependent manner (Oyama et al, 2005). The prognosis of a patient with AIPT is poor, with a 10 to 23% mortality rate (Vrobel et al, 1989;Oyama et al, 2005).…”
Section: Introductionmentioning
confidence: 99%